DINAMIKA MODEL KEPEMIMPINAN KEPALA SEKOLAH EFEKTIF DALAM MENINGKATKAN KOMPETENSI GURU - Susandi Armanto (UNISAN JURNAL, 2024)
Education in schools is said to be of good quality if the inputs needed in the learning process are adequate, such as educator resources, facilities, management and so on. Likewise, education is said to be of quality if the education process is carried out in a transparent and accountable manner, the output produced from the learning process is in accordance with the national graduation standards set by the government. Meanwhile, teachers have the main task of (1) making learning programs; (2) implementing learning programs; (3) carry out evaluations; (4) carry out analysis of student learning outcomes; (5) carry out repair, remedial, and enrichment. Not all teachers are able to carry out the main task. Many factors influence. The two main factors are ability and will. Coordinates of ability and willingness will greatly affect teacher performance. The principal besides being tasked with fostering teacher competence also functions as a motivator. Each element of the leadership should be able to move other people, both subordinates and colleagues, so that they are consciously and collectively willing to behave to achieve the goals that have been set. This research uses data collection techniques with interview methods, and documentation methods. The technique of guaranteeing the validity of the data in this study is triangulation of sources and triangulation of data collection techniques. Qualitative data analysis in this study is descriptive data consisting of three activities that take place simultaneously. Namely data reduction, data presentation and conclusion drawing. The results of the research and analysis can be concluded that the principal’s contribution is to increase teacher professionalism in learning planning, learning implementation, and learning evaluation